Knowledge and Perceptions of Dental Students Regarding Vape (E-Cigarette) Usage in Karachi: A Multicenter Cross-Sectional Study - Asalan Mirza; Aisha Wali; Saleem Ullah Abro; Shakila Nazir; Maryam Riaz; Muhammad Khan (Journal of Aziz Fatimah Medical and Dental College)
Objective: To investigate the knowledge, perceptions, and associated factors influencing Vape (E-cigarette) use among dental students in Karachi, Pakistan.